Based on visual thinking analyzing the image of woodblock prints in Foshan - Ramli, Sharulnizam Bin; Juan, Zhou Lin (Edelweiss Applied Science and Technology, 2025)
With the rapid socio-economic transformation and modernization in China, the transmission of traditional folk culture faces significant challenges. As an important branch of Chinese New Year woodblock prints, Foshan woodblock prints have gradually lost their cultural and market significance due to declining market demand and the modernization of living environments. Although designated as a national intangible cultural heritage, its preservation is still at risk, particularly with the potential loss of traditional craftsmanship. To deeply explore the visual characteristics and cultural expression of Foshan woodblock prints, this study applies Arnheim’s Visual Thinking theory, employing qualitative research and case analysis. The focus is placed on the existing workshop “Feng Junji,” examining its common visual symbols and cultural connotations. This research aims to provide theoretical support for the protection of intangible cultural heritage and inspire innovative applications of traditional visual elements in modern design.